1995
DOI: 10.1002/cne.903550303
|View full text |Cite
|
Sign up to set email alerts
|

Multiple gonadotropin‐releasing hormone (GnRH)‐immunoreactive systems in the brain of the dwarf gourami,Colisa lalia: Immunohistochemistry and radioimmunoassay

Abstract: The present study characterizes gonadotropin-releasing hormone (GnRH) neuronal groups that are located in several different brain regions by investigating GnRH molecular species and projection patterns in an anabantid fish, Colisa lalia. First, we examined the molecular species of GnRHs in extracts of the brain and the pituitary by reverse-phase high-performance liquid chromatography followed by radioimmunoassays. We found salmon GnRH (sGnRH), chicken GnRH-II (cGnRH-II), and an unfamiliar GnRH-like substance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
131
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(138 citation statements)
references
References 68 publications
7
131
0
Order By: Relevance
“…In fish, as in other vertebrates, several authors (e.g. Amano et al 1991, Grober et al 1994, Yamamoto et al 1995 have proposed the existence of at least two distinct GnRH neuronal systems. The cGnRH-II system predominates in the midbrain, while the second variant occurs in the pre-optic area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fish, as in other vertebrates, several authors (e.g. Amano et al 1991, Grober et al 1994, Yamamoto et al 1995 have proposed the existence of at least two distinct GnRH neuronal systems. The cGnRH-II system predominates in the midbrain, while the second variant occurs in the pre-optic area.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of the GnRH innervation of the pituitary gland (e.g. Kah et al 1986, Amano et al 1991, Rosenblum et al 1994, Yamamoto et al 1995 suggested that, in fish, sGnRH may have a more important role to play in pituitary gland function than cGnRH-II.…”
Section: Introductionmentioning
confidence: 99%
“…21C), suggesting that sGnRH neurons in the OB and the TN are not involved in the regulation of gonadal maturation. In the dwarf gourami, GnRH originating from the TN does not affect GTH secretion but rather has a function as a neuromodulator in the brain (Oka and Ichikawa 1990;Oka 1992;Yamamoto et al 1995). sGnRH originating from the TN is also not considered to be essential for gonadal development in goldfish (Kobayashi et al , 1994Kim et al 2001).…”
Section: -2 Changes In Sgnrh Mrna Expression During Gonadal Maturatmentioning
confidence: 99%
“…1) (Oka and Matsushima, 1993;Kim et al, 1995;Yamamoto et al, 1995), indicating that the neural circuits of the olfactory bulb are major targets of neuromodulation by GnRH in these species. However, to date no published studies have examined the physiological effects of GnRH in the olfactory bulb; the data available at present only allow us to speculate on the possible neuromodulatory functions of GnRH in the olfactory bulb.…”
Section: Modulation In the Olfactory Bulbmentioning
confidence: 99%